On freshwater fluxes and the Atlantic meridional overturning circulation. Issue 2 (16th January 2020) - Cael, B. B.; Jansen, Malte F.
Abstract: We address the role of freshwater forcing in the modern day ocean. Specifically, we ask the question of whether an amplification of the global freshwater forcing pattern leads to a strengthening or weakening of the steady‐state Atlantic Meridional Overturning Circulation (AMOC). While the role of freshwater forcing in the AMOC has received much attention, this question remains unresolved, in part because past studies have primarily investigated idealized models, large regime shifts away from the modern ocean state, or coupled atmosphere–ocean simulations on shorter timescales than required for the deep ocean to equilibrate. Here we study the AMOC's sensitivity at equilibrium to small perturbations in the magnitude of the global freshwater fluxes in simulations performed with a realistically configured ocean circulation model. Our results robustly suggest that for the equilibrium state of the modern ocean, freshwater fluxes strengthen the AMOC, in the sense that an amplification of the existing freshwater flux‐forcing pattern leads to a strengthening of the AMOC and vice versa. A simple physical argument explains these results: the North Atlantic is anomalously salty at depth and increased freshwater fluxes act to amplify that salinity pattern, resulting in enhanced AMOC transport.